The relationship between voluntary employer change and work ability among older workers: investigating the honeymoon-hangover effect - Nina Garthe; Hans-Martin Hasselhorn (Journal for Labour Market Research, 2021)
The aim of the study was to investigate the effect of voluntary employer changes on self-reported work ability among older workers in Germany and whether a honeymoon-hangover effect (HHE) exists here. In research on job satisfaction, three typical periods around a voluntary employer change characterize a HHE: a deterioration in the old job (deterioration), an initial increase in the new job (honeymoon) and a subsequent decline over time (hangover). Whether a HHE exists in respect to work ability following a voluntary employer change remained open. The analyses are based on data from the first three waves of the lidA study (2011, 2014, 2018), a representative cohort study of older employees in Germany born in 1959 or 1965. Data from 2502 workers who participated in all three study waves was analyzed. Fixed-effects regression analyses including lag and lead variables were conducted. A deterioration, honeymoon and hangover period were found. Work ability increased substantially following the voluntary employer change. Our study shows that voluntary employer changes have the potential to maintain work ability at higher working age, but not to increase the work ability in the long-term perspective. However, despite the existence of a hangover period, the positive overall effect of the voluntary change should not be underestimated.
Keywords: 330; Turnover; Older workers; Work ability; Honeymoon-hangover effect; Cohort study; Fixed-effects regression